Integrating new habits and practices data and homecare products into the Creme RIFM aggregate exposure model - Isabelle Lee; Ben Smith; Brendan Ring; Catherine Barratt; Cesar Scrochi; Fanny Boisleve; Gretchen Ritacco; John O'Brien; John Ryan-Purcell; Nikaeta Sadekar; Olivia Payne; Ruari Zink; et al. (Regulatory Toxicology and Pharmacology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Factors affecting short-term post-release survival probability of Lake Trout implanted with acoustic telemetry transmitters - Alexander J. Gatch; Dimitry Gorsky; Kyle T. Morton; R. Josephine Johnson; Collin J. Farrell; Timothy B. Johnson; Emma J. Bloomfield; Brent Metcalfe; Jessica Goretzke; Michael Connerton; Sarah M. Larocque; Jonathan D. Midwood; et al. (Fisheries Research, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Biotransformation of 6:2/4:2 fluorotelomer alcohols by Dietzia aurantiaca J3: Enzymes and proteomics - Shefali Bhardwaj; Matthew Lee; Denis O'Carroll; James McDonald; Keith Osborne; Stuart Khan; Russell Pickford; Nicholas Coleman; Casey O’Farrell; Sarah Richards; Michael J. Manefield (Journal of Hazardous Materials, 2024)

Imidacloprid exposure is detectable in over one third of wild bird samples from diverse Texas ecoregions - Meredith J. Anderson; Alan Valdiviezo; Mark H. Conway; Christina Farrell; R. Keith Andringa; Amy Janik; Weihsueh A. Chiu; Ivan Rusyn; Sarah A. Hamer (Science of The Total Environment, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Exploring veterinarians' behaviour relating to antibiotic use stewardship on Irish dairy farms using the COM-B model of behaviour change - Sarah Farrell; Tony Benson; Claire McKernan; Áine Regan; Alison M.G. Burrell; Moira Dean (Research in Veterinary Science, 2023)

Genotypic differences in vase life of Anthurium andraeanum (Hort.) cut-flowers are associated with differences in spathe chlorophyll content - Sarah Evelyn; Winston Elibox; Pathmanathan Umaharan; Kathryn De Abreu; Aidan D. Farrell (Postharvest Biology and Technology, 2023)

Using Protection Motivation Theory to Predict Intentions for Breast Cancer Risk Management: Intervention Mechanisms from a Randomized Controlled Trial - Claire C. Conley; Karen J. Wernli; Sarah Knerr; Tengfei Li; Kathleen Leppig; Kelly Ehrlich; David Farrell; Hongyuan Gao; Erin J. A. Bowles; Amanda L. Graham; George Luta; Jinani Jayasekera; et al. (Journal of Cancer Education, 2023)
The purpose of this study is to evaluate the direct and indirect effects of a web-based, Protection Motivation Theory (PMT)–informed breast cancer education and decision support tool on intentions for risk-reducing medication and breast MRI among high-risk women. Women with ≥ 1.67% 5-year breast cancer risk ( N = 995) were randomized to (1) control or (2) the PMT-informed intervention. Six weeks post-intervention, 924 (93% retention) self-reported PMT constructs and behavioral intentions. Bootstrapped mediations evaluated the direct effect of the intervention on behavioral intentions and the mediating role of PMT constructs. There was no direct intervention effect on intentions for risk-reducing medication or MRI ( p ’s ≥ 0.12). There were significant indirect effects on risk-reducing medication intentions via perceived risk, self-efficacy, and response efficacy, and on MRI intentions via perceived risk and response efficacy ( p ’s ≤ 0.04). The PMT-informed intervention effected behavioral intentions via perceived breast cancer risk, self-efficacy, and response efficacy. Future research should extend these findings from intentions to behavior. ClinicalTrials.gov Identifier: NCT03029286 (date of registration: January 24, 2017).

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mechanisms in mutualisms: a chemically mediated thrips pollination strategy in common elder - Alison S. Scott-Brown; Sarah E. J. Arnold; Geoffrey C. Kite; Iain W. Farrell; Dudley I. Farman; Dominique W. Collins; Philip C. Stevenson (Planta, 2019)

Contrasting latitudinal gradients of body size in helminth parasites and their hosts - Tad Dallas; Alyssa‐Lois M. Gehman; A. Alonso Aguirre; Sarah A. Budischak; John M. Drake; Maxwell J. Farrell; Ria Ghai; Shan Huang; Ignacio Morales‐Castilla (Global Ecology and Biogeography, 2019)
Aim We examined body size scaling relationships for two developmental life stages of parasitic helminths (egg and adult) separately in relationship to latitude (i.e. Bergmann's rule), temperature and temperature seasonality. Given that helminth eggs experience environmental conditions more directly, whereas adults live inside infected host individuals, we predict stronger environmentally driven gradients of body size for eggs than for adults. Location Global. Time period Present day. Major taxa studied Parasitic helminths. Methods We compiled egg size and adult body size data (both minimum and maximum) for 265 parasitic helminth species from the literature, along with species latitudinal distribution information using an extensive global helminth occurrence database. We then examined how the average helminth egg and adult body size of all helminth species present (minimum and maximum separately) scaled with latitude, temperature and temperature variability, using generalized linear models. Results Both the egg size and the adult body size of helminths tended to decrease towards higher latitudes, although we found the opposite body size scaling pattern for their host species. Helminth sizes were also positively correlated with temperature and negatively, but more weakly, with temperature seasonality. Main conclusions Instead of following the body size patterns of their hosts, helminth parasites are more similar to other ectotherms in that they follow the converse Bergmann's rule. This pattern did not differ between helminth developmental stages, suggesting that mean annual temperature and seasonality are unlikely to be related mechanistically to body size variation in this case.

The Nine Habits of successful comprehensive cancer control coalitions - Karin Hohman; Leslie Given; Margaret Farrell; April Barry; Linda Robertson; Sarah Kerch; Sarah Shafir (Cancer Causes & Control, 2018)

Evaluating local adaptation of a complex phenotype: reciprocal tests of pigmy rattlesnake venoms on treefrog prey - Sarah A. Smiley-Walters; Terence M. Farrell; H. Lisle Gibbs (Oecologia, 2017)

Global Mammal Parasite Database version 2.0 - Patrick R. Stephens; Paula Pappalardo; Shan Huang; James E. Byers; Maxwell J. Farrell; Alyssa Gehman; Ria R. Ghai; Sarah E. Haas; Barbara Han; Andrew W. Park; John P. Schmidt; Sonia Altizer; et al. (Ecology, 2017)
Illuminating the ecological and evolutionary dynamics of parasites is one of the most pressing issues facing modern science, and is critical for basic science, the global economy, and human health. Extremely important to this effort are data on the disease‐causing organisms of wild animal hosts (including viruses, bacteria, protozoa, helminths, arthropods, and fungi). Here we present an updated version of the Global Mammal Parasite Database, a database of the parasites of wild ungulates (artiodactyls and perissodactyls), carnivores, and primates, and make it available for download as complete flat files. The updated database has more than 24,000 entries in the main data file alone, representing data from over 2700 literature sources. We include data on sampling method and sample sizes when reported, as well as both “reported” and “corrected” (i.e., standardized) binomials for each host and parasite species. Also included are current higher taxonomies and data on transmission modes used by the majority of species of parasites in the database. In the associated metadata we describe the methods used to identify sources and extract data from the primary literature, how entries were checked for errors, methods used to georeference entries, and how host and parasite taxonomies were standardized across the database. We also provide definitions of the data fields in each of the four files that users can download.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)